Ecological analysis of cholera hot spots in Africa - (:unkn) unknown (My University, 2021)
Cholera is a severe acute diarrhoeal disease caused by Vibrio cholerae, a gram-negative bacterium that colonises warm, saline, alkaline surface waters, often in association with phytoplankton or zooplankton. After 50 years of introduction of cholera in Africa, the disease is affecting African countries in a very strong way. The objective of the PhD work was to try to elucidate the causes of cholera endemicity in Africa and on the scale of a rift sector, Lake Kivu and the Katana he...
Keywords: African Research